Pricing in Abundance: The Economics of the Manatua Cable - De Ridder, John (Journal of Telecommunications and the Digital Economy, 2020)
Small island nations that have relied on satellites for international connectivity are now being connected by submarine cables that have infinitely more capacity. The hope is that these cables will lift the social and economic development of the economies connected. This hope is more likely to be realized with the adoption of wholesale traffic pricing based on the capacity abundance brought by the cable system rather than historical wholesale bandwidth pricing, which assumes capacity scarcity. Reductions in the wholesale cost of international connectivity are more likely to be passed on to end users if there is retail competition. The proposed wholesale pricing model facilitates increased retail competition. These ideas are explored in a case study of the Cook Islands, which is a member of the Manatua Cable Project.